KEANEKARAGAMAN ARTHROPODA PADA TANAMAN BAWANG MERAH DI LAHAN YANG DIAPLIKASI FORMULASI BIOPESTISIDA DI KABUPATEN NGANJUK - Hendra Wahyudi Ariyono; Sri Wiyatiningsih; Wiwin Windriyanti (UPN VETERAN JAWA TIMUR, 2022)
Shallots (Allium cepa L.) are one of the leading vegetable commodities that have been intensively cultivated by farmers for a long time. A large percentage of damage to plants can result in reduced tuber weight. Study of insect diversity is the first step in pest control and pest management in crops. The purpose of this study, namely, to determine the diversity index of pests and natural enemies in shallot plantations after the use of biopesticide and chemical pesticide formulations. The research was carried out from December 2020 to February 2021. The study was conducted in Sukorejo Village, Rejoso District, Nganjuk Regency with an altitude of 140 m above sea level where fobio (biopesticide formulation) and chemical insecticides were applied. The area of the research area is about 140 m², where there are 2,400 shallot plant populations. This study used a non-factorial randomized block design (RAK) method. There were 4 treatments which were repeated 6 times to obtain 24 experimental units. Each experimental unit consisted of 100 shallot plants with a spacing of 18 x 14 m and a barrier distance of 50 cm. The results showed. Based on observations, the total number of arthropods found in shallot plantations in 5 observations was 1391 individuals consisting of seven orders of insects and one order of polypods. The highest diversity index was in treatment B (semi organic) because the combination of NPK fertilizer and spraying fobio on plants could increase insect diversity.